Impact of fulvic acids on bio-methanogenic treatment of municipal solid waste incineration leachate. (1st December 2016) - Dang, Yan; Lei, Yuqing; Liu, Zhao; Xue, Yiting; Sun, Dezhi; Wang, Li-Ying; Holmes, Dawn E.
Abstract: A considerable amount of leachate with high fulvic acid (FA) content is generated during the municipal solid waste (MSW) incineration process. This incineration leachate is usually processed by downstream bio-methanogenic treatment. However, few studies have examined the impact that these compounds have on methanogenesis and how they are degraded and transformed during the treatment process. In this study, a laboratory-scale expanded granular sludge bed (EGSB) reactor was operated with MSW incineration leachate containing various concentrations of FA (1500 mg/L to 8000 mg/L) provided as the influent. We found that FA degradation rates decreased from 86% to 72% when FA concentrations in the reactor were increased, and that molecular size, level of humification and aromatization of the residual FA macromolecules all increased after bio-methanogenic treatment. Increasing FA influent concentrations also inhibited growth of hydrogenotrophic methanogens from the genus Methanobacterium and syntrophic bacteria from the genus Syntrophomonas, which resulted in a decrease in methane production and a concomitant increase in CO2 content in the biogas. Sequences most similar to species from the genus Anaerolinea went up as FA concentrations increased. Bacteria from this genus are capable of extracellular electron transfer and may be using FA as an electron acceptor for growth or as a shuttle for syntrophic exchange with other microorganisms in the reactor. In order to determine whether FA could serve as an electron shuttle to promote syntrophy in an anaerobic digester, co-cultures of Geobacter metallireducens and G. sulfurreducens were grown in the presence of FA from raw leachate or from residual bioreactor effluent. While raw FA stimulated electron transfer between these two bacteria, residual FA did not have any electron shuttling abilities, indicating that FA underwent a significant transformation during the bio-methanogenic treatment process. These results are significant and should be taken into consideration when optimizing anaerobic bioreactors used to treat MSW incineration leachate high in FA content. Graphical abstract: Highlights: High fulvic acid content adversely affects methanogenesis in anaerobic digesters. Humification and aromatization of fulvic acids increases during biomethanogenesis. Fulvic acids from incineration leachate can promote syntrophy between bacteria. Treated fulvic acids lose their electron shuttling capabilities. Microbial community structure is impacted by the presence of fulvic acids.